Abuela's special letters ebook - Jules, Jacqueline (Sofia Martinez., 2017)
Sofia is on a mission to make a family time capsule. The whole family contributes pictures and special items. Abuela even writes a letter to each of her grandchildren to be opened in fifteen years. Can Sofia really wait fifteen years to find out what that letter says? Adorable art, a table of contents, writing prompts, discussion questions, and an English/Spanish glossary are all included in this early chapter book.